Incorporating the sampling effectiveness of detection dogs in the faecal standing crop method - Da Silva, Amanda R.; De Oliveira, Márcio L.; Duarte, José M. B. (European journal of wildlife research, 2020)
Evaluating the population status of elusive and rare species is a challenge for wildlife managers and conservationists. A promising method that has been used is faecal pellet counting applied to the faecal standing crop (FSC) method. The FSC method estimates population density based on faecal pellets counted in a given area by using parameters such as defecation rate and faecal persistence, which vary according to the environment. The search for faeces has become more effective with the help of scat detection dogs, which have a better detection rate compared to humans. Therefore, we aimed to incorporate the sampling effectiveness of scat detection dogs as parameters in FSC methods. For this purpose, two experiments were conducted to evaluate the detectability of Mazama faeces related to their distance from a search transect and their age (time since deposition). Our results show that incorporating scat detection dog parameters can result in density estimates three times higher than those reached without incorporating the detection dog parameters in FSC methods.